Multifactorial Analysis of Wood Deterioration in Ancient Egypt: A Case Study of Khufu’s Second Solar Boat - Shimaa Ibrahim; Paola Grenni; Lucia Mancini; Marco Voltolini; Hanan Mohamed Kamal Abdel-Fatah; Ahmed Refaat; Dina M. Atwa (Applied Sciences)
This study presents a multi-analytical investigation of the wooden components from Khufu’s Second Solar Boat, one of the valuable archaeological discoveries in ancient Egypt. The research integrates advanced imaging and analytical techniques to identify wood species, assess deterioration patterns, and characterize the fungal and bacterial biodeteriogens. The initial visual examination documented the state of preservation at the time of discovery. Subsequently, the identification of the wood species was carried out. The deterioration status was assessed using a variety of tools, including scanning electron microscopy (SEM) and high-resolution synchrotron radiation computed microtomography (SR-μCT) for morphological alterations, X-ray diffraction (XRD) for crystallinity changes and Fourier-transform infrared spectroscopy (FTIR) to assess chemical degradation indexes of wood. Moreover, molecular techniques were used to identify and characterize the presence of biodeterioration agents. Results indicate that ancient craftsmen used cedar wood for the boat construction. The analysed samples exhibited advanced biotic and abiotic degradation, as evidenced by microbiological assessments, XRD measurements of cellulose crystallinity, FTIR indices, SEM micrographs and SR-μCT data. These results provide crucial insights into the long-term degradation processes of archaeological wood in arid environments, enhancing our understanding of ancient Egyptian woodworking practices and informing future conservation strategies for similar artifacts.